Resultados do tratamento com estimulação do nervo vago em dez pacientes com epilepsia refratária - MACIEL, Brenda Gonçalves (2018)
The epilepsy is a neurological disease that affects about 70 million people worldwide. The first line of treatment consists of antiepileptic drugs (AEDs) that are widely used in crisis management. We say that epilepsy is refractory, intractable or drug-resistant, when control is not achieved with the use of 2 or more drugs appropriately indicated for the type of seizure. The management of refractory epilepsy is divided into three main categories: pharmacotherapy, epilepsy surgery and alternative treatment strategies, including neurostimulation, ketogenic diet and lifestyle changes. When surgical treatment is not indicated or there is no improvement after it, neuromodulator treatment is started, which seeks a suppression or reduction in the number of seizures. The vagus nerve stimulator acts both reducing seizures, as in depression, improving the life quality of the patient and the family.